Antiviral effect of synthetic derivatives of nucleotides and nucleosides against DNA and RNA viruses - Zouharová, Darina; Turánek, Jaroslav, 1958-; Masarykova univerzita. Ústav biochemie (2018)
Práce se zabývá látkami nukleotidového a nukleosidového charakteru, které vykazují antivirální účinek. Dále je v práci pojednáno o liposomálních nosičích, které jsou vhodným nanopartikulárním systémem pro cílení léčiv včetně antivirotik. Herpesviry a flaviviry představují významnou skupinu lidských a zvířecích patogenů. Proti naprosté většině flavivirů význačných z medicínského hlediska nejsou komerčně dostupná antivirotika a schválená terapie. Úspěšná antivirová léčba je dostupná proti řadě herpesvirů. V případě Aujeszkyho choroby však doposud nebyla schválena žádná účinná chemoterapie. Značnou komplikaci v léčbě virových infekcí představuje vznik rezistentních forem. Z těchto důvodů je cílem předkládané práce nalézt vhodné látky pro inhibici virové infekce. Nukleosidové analogy jsou základními terapeutiky pro léčbu virem infikovaných pacientů, proto byla vybrána série látek z této skupiny pro testování antivirálního účinku proti zvoleným herpesvirovým a flavivirovým patogenům. V příp
The thesis deals with compounds of nucleotide and nucleoside character, which have an antiviral effect. Furthermore, the thesis deals with liposomal carriers, a suitable nanoparticular drug targeting system including antivirals. Herpesviruses and flaviviruses represent a group of medically important pathogens of humans and animals. There are no available antivirals and approved therapy against most flaviviruses. A successful antiviral treatment is available against a number of representatives of the Herpesviridae family. No effective chemotherapy has been approved for Aujeszky’s disease so far. A major complication in the treatment of viral infections is the emergence of drug resistant forms. For these reasons, the aim of the present thesis is to find suitable agents for inhibiting viral infections. Nucleoside analogues are basic therapeutic for the treatment of virus infected patients, therefore a series of compounds from this class has been chosen to evaluate their antiviral activity
Vedoucí práce: Jaroslav Turánek
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2018
Keywords: disertace; dissertations; Drug Delivery Systems; antivirotika; flaviviry; herpetické viry; lipozomy; Nukleosidové analogy; lékové transportní systémy; antiviral agens; flaviviruses; herpesviruses; liposomes; nucleoside analogues